ASSESSMENT OF KNOWLEDGE ABOUT EVIDENCE BASED MEDICINE IN MEDICAL STUDENTS AND DOCTORS IN A PAKISTANI HEALTH CARE SETTING - Irshad, Abeer; Ramzan, Musarat; Iqbal, Mobeen (Journal of Ayub Medical College Abbottabad, 2010)
Background: Evidence based practice promotes self assessment and ensures delivery of up to date care to patients. The concept of Evidence Based Medicine (EBM) in developing countries is still in its infancy where strong opinions drive patient care. Methods: We conducted a cross sectional survey to explore the knowledge, perceptions and attitudes regarding EBM in final year medical students and physicians of our institution. The survey was distributed to all students and residents of the college and the affiliated hospital. Results: The response rate was 57% (74/130). Seventy-one percent (53/74) of respondents were not aware of EBM. Out of these, 38 were medical students and 15 were house officers. Only 16 (9 students and 7 doctors) admitted that they had heard about EBM. Those who heard about EBM recognised its importance in patient care. Teaching at both under- and postgraduate level was strongly suggested. Participants recognised the need for EBM skills and expertise. Financial constraint was considered as the main hindrance in practicing EBM. Conclusion: The concept of EBM is still alien to most of the students and residents at our institution. There is need for incorporating formal teaching of EBM at all levels of medical education. Keywords: Medical education, Evidence based medicine, Undergraduates